Juvenile delinquency - Kenty-Drane, Jessica L. (Men and masculinities: a social, cultural, and historical encyclopedia, 2004)
This reference analyzes, summarizes, and explains the complexities of men's lives and the idea of modern manhood. It looks at literature, art, and music from a gender perspective, and covers intimacy, sexual violence, pornography, sexism and rituals.
OCLC: 301173623
Keywords: dept.soc